2009
DOI: 10.1007/s12562-009-0161-6
|View full text |Cite
|
Sign up to set email alerts
|

A serine proteinase from the sarcoplasmic fraction of red sea bream Pagrus major is possibly derived from blood

Abstract: Collagen degradation is known to be involved in post mortem tenderization of fish muscle. A serine proteinase which is assumed to be related to collagen degradation after fish death was purified from sarcoplasmic fraction of red sea bream Pagrus major by ammonium sulfate fractionation and column chromatographies on Sephacryl S-300, Q Sepharose and Phenyl Sepharose CL-4B. The enzyme hydrolyzed gelatin and was obtained as a protein band of approximately 38 kDa on sodium dodecyl sulfate polyacrylamide gel electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Gelatinolytic proteinases were detected in red sea bream muscle, gelatinolytic proteinase at 85 kDa was serine proteinase, but two gelatinolytic enzymes at 55 and 52 kDa were metalloproteinases (Wu et al 2010a,b). Yoshida et al (2009) reported that a gelatinolytic serine proteinase was 38 kDa. We also found two gelatinolytic proteinases (90 and 70 kDa) in common carp muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gelatinolytic proteinases were detected in red sea bream muscle, gelatinolytic proteinase at 85 kDa was serine proteinase, but two gelatinolytic enzymes at 55 and 52 kDa were metalloproteinases (Wu et al 2010a,b). Yoshida et al (2009) reported that a gelatinolytic serine proteinase was 38 kDa. We also found two gelatinolytic proteinases (90 and 70 kDa) in common carp muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatinolytic serine proteinases were detected in many fish species by gelatin zymography, including red stingray wing ( Dasyatis akajei ) (Bae et al . 2010), red sea bream ( Pagrus major ) (Yoshida et al . 2009; Wu et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation